Analysis of Work Discipline on the Effectiveness of Employees at the Medan Mayor's Office - Fahrul Azhar Kesogihin; Andri Soemitra (Penerbit Jurnal Indonesia, 2022)
Discipline can be interpreted as a person's awareness and willingness to obey agency regulations and applicable norms. Discipline for agencies or companies that need to be improved is aimed at improving performance and high productivity. This study aims to see how work discipline on the work effectiveness of employees at the Medan mayor's office. The research methodology used in this research is to use qualitative methods. The results show that work discipline is very influential on the work effectiveness of employees at the Medan mayor's office.